The diagnosis of pulmonary tuberculosis by gaschromatographic detection of tuberculostearic acid using flame ionisation detectors - Herz, Arnd; Leichsenring, Michael; Felten, Michael; Oosthuizen, O. J.; Mayatepek, Ertan; Haas, Walter; Bremer, Hans J. (European journal of clinical investigation, 1994)
Abstract. It has been shown that the detection of tuberculostearic acid (TBSA) with gas chromatography-massspectrometry provides a highly specific, sensitive and rapid method for the diagnosis of various forms of tuberculosis. However, the need for complex and expensive equipment prevented the more widespread use of this method. We report on the application of conventional gas chromatography with flame ionization detectors in the detection of TBSA in sputum samples. TBSA was detected in all patients with proven pulmonary tuberculosis before treatment or under treatment for less than 4 weeks (n= 18). Six of these patients (33%) had a negative microscopy result at the time of the study. Sputum samples from patients under therapy for longer than 4 weeks (n= 20) were TBSA-positive in 15 cases (75%). Only in two cases was the diagnosis by microscopy and/or cultur not met by TBSA-detection. All sputa of 20 control patients with lung diseases other than tuberculosis were TBSA negative. Additional analysis of patients' data showed a significant relationship (P <0·005) between the relative amounts of TBSA detectable in the sputum samples and the duration of therapy. It is concluded that conventional capillary gaschromatography may be sensitive and specific enough to be used for the detection of TBSA in sputum of patients with pulmonary tuberculosis.